Pengaruh Pemberian Pelayanan Antenatal Care 10T Terhadap Kunjungan Ibu Hamil di Puskesmas Haruai - Handayani, Puspita; Yunita, Laurensia; Hidayah , Nur (Pusat Riset dan Inovasi Nasional, 2024)
The Maternal Mortality Rate (MMR) in Indonesia which is quite high every year makes homework for the government. The government effort to reduce MMR requiring pregnant women to go for antenatal care the nearest health facility. Success in antenatal care service is measured through indicator coverage of antenatal service, there’s K1, K4 and K6. Look at data from the Haruai Health Center for K1, K4 and K6 the Haruai Health Center is ranking 15, 12 and 15 of 18 Health Center in Tabalong Regency. Based on these data it can be seen that visit in the Haruai Health Center area is very low. The Objective is to Analyze the effect of antenatal care 10T service visit of pregnant women at the Haruai Health Center. This research uses quantitative descriptive research. The sample is pregnant women in their third trimester, totaling 39 respondents. Sample using accidental sampling technique. Data collection used questionnaire, then data were analyzed using chi-square test, with significance level of 95% (α : 0,05). Result of the research, third trimester pregnant women who didn’t receive standard antenatal care 10T examinations were 66,7% of respondents, and third trimester pregnant women who no have visits according to quantity standards as much as 89,7% of respondents. The results of bivariate analysis p-value is 0,009<value α:0,05 which means there’s a significant relationship between antenatal care 10T and visit to pregnant women. Concluded that there’s an effect on the provision of services between antenatal care 10T on visits to pregnant women